Neuropathic pain treatment and research: experiences from the United Kingdom mission to Afghanistan and future prospects. Issue 3 (6th September 2017) - Wood, Paul; Small, C; Lewis, S; Mahoney, P
Abstract : The Defence Medical Services (DMS) of the United Kingdom (UK) assumed command of the Role 3 Medical Treatment Facility field hospital during Operation HERRICK in Afghanistan from April 2006 until the final drawdown in November 2014. The signature injury sustained by coalition personnel during this period was traumatic amputation from improvised explosive devices. Many patients who had suffered extensive tissue damage experienced both nociceptive and neuropathic pain (NeuP). This presented as a heterogeneous collection of symptoms that are resistant to treatment. This paper discusses the relationship of NeuP in the context of ballistic injury, drawing in particular on clinical experience from the UK mission to Afghanistan, Operation HERRICK. The role of this paper is to describe the difficulties of assessment, treatment and research of NeuP and make recommendations for future progress within the DMS.